Novel synthetic routes towards azaindoles, Exploring one-pot metal-catalysed reactions - Mortinho, Ana Cristina da Costa (2021)
Azaindoles are heterocyclic compounds scarce in nature, although interesting scaffolds in medicinal chemistry so there is a need of developing sustainable synthetic methods to obtain these cores. To date several methods involving more than one metal-catalysed reaction, like C-N cross-coupling,Heck coupling or the Sonogashira have been developed towards azaindoles. However, these methods require the use of amino-halopyridines as starting materials, which are difficult to prepare. This project aimed to surpass the need of functionalization of aminopyridines conceiving a fast and scalable one-pot methodology towards azaindole synthesis. The first strategy envisaged a well-established reaction in our group, the C-N cross-coupling reaction, to prepare an imine/enamine in situ, followed by a C-H activation / oxidative cyclization reaction catalysed by a metal. The preliminary studies were made using 2,5-dimethylaniline and α-bromo styrene and other synthetized bromides. The indole compound II.2 was isolated in 50% yield, and under the same conditions different aminopyridines and bromides were tested using palladium catalysis in an unprecedented approach for azaindole synthesis. This strategy afforded only one regioisomer, a 4-azaindole (II.4) with a 70% yield and worked only with aminopyridines that possess electro-donating groups. However, this method proved to be limited to few substrates. Thus, an alternative approach was attempted in which the imines/enamines were formed in situ by condensation of an amine with a ketone, followed by C-H activation/oxidative cyclization catalysed by palladium. Preliminary studies were carried with 2,5-dimethylaniline and acetophenone and afforded the corresponding indole II.2 in 51% yield. Next, the same strategy was applied to aminopyridines. The reaction demonstrated to be effective when acetophenones were used. Thus, a variety of 4-azaindoles (14 examples, 13 synthesized in this thesis) were synthesized by this methodology with yields ranging from 24 % up to 96%, possessing electron-withdrawing and electron donating groups. The method developed consists on a simple protocol, a one-pot reaction, involving a C-H activation reaction scarcely explored in the synthesis of this class of compounds.